Dietary habits and food intake frequency of preschool children. Issue 4 (10th July 2017) - Rysha, Agim; Gjergji, Tahire M.; Ploeger, Angelika
Abstract : Purpose: The study aims to assess the dietary habits and frequency of food intake by preschool-aged children in Kosovo. Design/methodology/approach: The study is based on a survey of meal patterning and frequency of food group intake, using a combined 24-hour recall and Dietary history questionnaires. The assessment took place in different towns of Kosovo. Parents completed 232 questionnaires with data on dietary habits and food frequency intake of their children. Intake frequencies were computed and included in the analyses. Findings: Dietary habits and frequency of food intake for specific foods (the main typical foods from the food groups) did not show significant differences ( P > 0.05) between age groups, except in terms of milk consumption ( P < 0.05) and soft drinks intake ( P < 0.001). It was found that the consumption of fruits and vegetables as well as other high-fiber foods is very limited. Research limitations: Despite the limitation in terms of sample, the results can be used by Kosovo's authorities as an indication for an assessment of child's development patterns in the country. Originality/value: This assessment reports for the first time the dietary habits and frequency of food intake by preschool-aged children in Kosovo. The dietary pattern was shown to be low in wholegrain products and fruits and vegetables, and high in soft drinks and sweet and salty foods. Health and education authorities should develop national programs and dietary guidelines on recommended dietary intakes.